Towards fair and effective North-South collaboration: realising a programme for demand-driven and locally led research - Maarten Olivier Kok; John Owusu Gyapong; Ivan Wolffers; David Ofori-Adjei; Elis Joost Ruitenberg (BMC, 2017)
Abstract Background At the turn of the 90s, studies showed that health research contributed little to health and development in low- and middle-income countries because it was oriented towards international priorities and dominated by researchers from the North. A new approach to North-South collaboration was required that would support demand-driven and locally led research in the South. The aim of this study was to analyse the development and functioning of a programme for demand-driven and locally led research in Ghana that was supported by a North-South collaboration. Methods For this mixed-method case study, we combined document analysis, key informant interviews and observation of programme events. Results The development of the research programme started with constructing a sponsorship constellation in the Netherlands. After highlighting the problems with traditional research collaboration, an advisory council formulated a vision for a more equal and effective approach to North-South collaboration. Together with Ghanaian partners, this vision was turned into a proposal for a Ghanaian-led programme for demand-driven and locally led research, which was funded by the Netherlands government. Research priority setting showed that the Ghanaian research needs were very different from the priorities of foreign funders and researchers. After a slow start, the number of locally submitted proposals increased from 13 in 2001 to 94 in 2005, revealing the existence of a substantial, but partly latent reservoir of research capacity. In total, 79 studies were funded. An impact evaluation showed that the results of the majority of the studies were used to contribute to action. Despite its success, the research programme came to an end in 2008 after the sponsorship constellation in the Netherlands fell apart. Conclusion Our study shows that realising a programme for demand-driven and locally led research in the South provides an effective approach to North-South collaboration in which results are used and local capacities and institutions are strengthened.